55.8k views
5 votes
Please help. Wrong answer will be reported

Please help. Wrong answer will be reported-example-1

1 Answer

1 vote

top:

(2x - 3y)^2

= 4x^2 - 12xy + 9y^2

bottom:

(3y - 2x)^2

= 9y^2 - 12xy + 4x^2

= 4x^2 - 12xy + 9y^2 (same as top)

so

(4x^2 - 12xy + 9y^2) / ( 4x^2 - 12xy + 9y^2) = 1

Ava is not correct. If you look at the denominator on her work:

[-(2x – 3y)]^2

= [(-1 )(2x – 3y)]^2

= (-1)^2 (2x – 3y)^2

= (2x – 3y)^2

so (2x – 3y)^2 / (2x – 3y)^2 = 1

The correct answer is 1

User Goddard
by
5.8k points